IMPACTS OF INFORMATION TECHNOLOGY ON BUSINESS PERFORMANCE OF SMALL-SIZED AGRIBUSINESS FIRMS - Toto Sugiharto (Jurnal Ilmiah Ekonomi Bisnis, 2011)
It has been identified that Small and Medium-sized Enterprises (SMEs) in Indonesia play an important role in the Indonesia’s economy. Its contribution to the national economy (i.e., GDP and export values), however, is relatively minimal as to compare with its unit numbers and number of labor involved. It is also of considerable lower than those of large-sized enterprises whose unit number and number of labor involved were much lower than those of SMEs. This, to some extent, indicates that SMEs’ productivity is relatively low. Some improvements are required accordingly. Information and communication technology, especially Internet technology application within SMEs is regarded to have the potentials to significantly increase their business performance. This study is aimed at investigating factors that potentially affect internet adoption and analyzing the impact of internet adoption on business performance of small-sized agribusiness firms. Modified Supply Process Model was adopted as an approach model in this study. One hundred and one small-sized agribusiness owners/operators were randomly selected as respondents. Primary data were collected and analyzed using path analysis. Results of the study showed that internet adoption within small-sized agribusiness owners/operators was significantly affected by perceived ease of use, internet self efficacy, internet anxiety, and personal innovativeness. Small-sized agribusiness firms’ business performance was affected by the level of internet adoption (i.e., non-adopter, potential adopter or adopter). This indicates that internet technology has the potentials to increase business performance.